South African trade unions and globalisation: going for the 'high road', getting stuck on the 'low road'. (1st April 2008) - ,; ,
Abstract : In this paper, we assess the South African labour movement's engagement with globalisation in the 1990s and its implications for labour politics in the following decade. Drawing on extensive archival research and interviews with key informants, we show that, although the labour movement had become committed to a 'high road', post-Keynesian restructuring vision by 1993, its representatives failed to pursue that vision consistently in the economic policy negotiations that preceded the historic 1994 democratic election. In fact, labour delegates actually agreed to several policy changes that were more in line with a 'low road', neo-liberal approach, with dramatic implications for workers in some sectors. The inability of labour's engagement with globalisation to benefit the working class has led to a long search for a new basis for union strategy.